2021
DOI: 10.1007/s12550-021-00424-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 13 Alternaria mycotoxins including modified forms in beer

Abstract: A multi-mycotoxin LC-MS/MS method was developed to quantify 13 free and modified Alternaria toxins in different beer types by applying a combination of stable-isotope dilution assays (SIDAs) and matrix-matched calibration. With limits of detection (LODs) between 0.03 µg/L (alternariol monomethyl ether, AME) and 5.48 µg/L (altenuene, ALT), limits of quantitation (LOQs) between 0.09 µg/L (AME) and 16.24 µg/L (ALT), and recoveries between 72 and 113%, we obtained a sensitive and reliable method, which also covers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…Geyer (Renningen, Germany), methanol (MeOH) from Honeywell Riedel-de Haën (Seelze, Germany), and acetonitrile (ACN) and the ammonia solution (25%) were purchased from VWR (Ismaning, Germany), all at least in analytical grade. Reference standards for TEN, ALT, and TeA were bought from Merck (Darmstadt, Germany), while AOH, AME, ATX I, ATX II, STTX III, ALTP, AOH-3-G, and AOH-9-G, AME-3-G as well as AOH-3-S and AME-3-S were either isolated out of fungal extracts or synthesized at our chair as described previously (Liu and Rychlik 2015;Scheibenzuber et al 2020Scheibenzuber et al , 2021. The stable isotope-labelled standards [ 2 H 4 ]-AOH, [ 2 H 4 ]-AME, and [ 13 C 6 , 15 N]-TeA were synthesized in our laboratory as reported in literature (Asam et al 2009(Asam et al , 2011a.…”
Section: Chemicals and Reference Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geyer (Renningen, Germany), methanol (MeOH) from Honeywell Riedel-de Haën (Seelze, Germany), and acetonitrile (ACN) and the ammonia solution (25%) were purchased from VWR (Ismaning, Germany), all at least in analytical grade. Reference standards for TEN, ALT, and TeA were bought from Merck (Darmstadt, Germany), while AOH, AME, ATX I, ATX II, STTX III, ALTP, AOH-3-G, and AOH-9-G, AME-3-G as well as AOH-3-S and AME-3-S were either isolated out of fungal extracts or synthesized at our chair as described previously (Liu and Rychlik 2015;Scheibenzuber et al 2020Scheibenzuber et al , 2021. The stable isotope-labelled standards [ 2 H 4 ]-AOH, [ 2 H 4 ]-AME, and [ 13 C 6 , 15 N]-TeA were synthesized in our laboratory as reported in literature (Asam et al 2009(Asam et al , 2011a.…”
Section: Chemicals and Reference Standardsmentioning
confidence: 99%
“…We then analyzed 50 barley samples and the respective standardized produced malts prepared from them to get a first insight into mycotoxin occurrence in barley and their possible formation during the malting process. In this study, the modified toxins AOH-3-G, AOH-9-G, AME-3-G, AOH-3-S, and AME-3-S were analyzed as well, which is quite important as data about those modified forms are still scarce and are only available for beer, sunflower oil, tomato products, cereals, fruits, and vegetables so far (Puntscher et al 2018;Scheibenzuber et al 2021;Walravens et al 2014Walravens et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the heterogeneous distribution of mycotoxins in food, the probable insufficient representation of consumption data, and the existence of multiple contamination sources, biomonitoring is recognized as a more effective and valuable approach [12][13][14], and has been successfully conducted to evaluate human exposure to different mycotoxins in Africa, Europe, Asia, and America [15][16][17][18][19]. With regard to Alternaria toxins, despite several external exposure assessments [3,5,[20][21][22][23], there were only limited reports on the biomonitoring approach. Asam et al, [24] and Hövelmann et al, [25] reported the detection of TeA in German individuals, while AOH was identified in urine samples from Portugal [26].…”
Section: Introductionmentioning
confidence: 99%
“…2752-Sunday, March 06, 2022 Interestingly, when the developed approach was applied for other mycotoxins (namely DON, AFB 1 , FB 1 , T-2, and OTA, no obvious biotransformation was observed at the conditions previously used for ZEN (Peters et al, 2021) indicating that different microorganisms have specific metabolic pathways for detoxification of different mycotoxins. For checking the concentrations of standards of conjugated mycotoxins, measurement of absorbance and calculation of concentrations via the molar absorption coefficients, as described by Scheibenzuber et al (2021) is highly recommended. Scheibenzuber et al (2021) also describe a method for determining molar absorption coefficients of previously uncharacterised conjugated mycotoxins.…”
Section: Quality Control Of Mycotoxin Analysesmentioning
confidence: 99%
“…For checking the concentrations of standards of conjugated mycotoxins, measurement of absorbance and calculation of concentrations via the molar absorption coefficients, as described by Scheibenzuber et al (2021) is highly recommended. Scheibenzuber et al (2021) also describe a method for determining molar absorption coefficients of previously uncharacterised conjugated mycotoxins.…”
Section: Quality Control Of Mycotoxin Analysesmentioning
confidence: 99%